ANALYSIS OF THE INFLUENCE OF ISLAMIC BANKING KNOWLEDGE, SOCIAL VALUES, RELIGIOUSNESS, AND PERCEPTIONS ON STUDENT CAREER INTEREST IN ISLAMIC BANKING (STUDY OF ISLAMIC BANKING STUDY PROGRAM STUDENTS IN SEMARANG CITY) - Rosana Dika Afristina; Muhammad Asrori; Sam'ani Sam'ani (Politeknik Negeri Semarang, 2023)
This study aims to analyse the significance of Islamic banking knowledge, social values, religiosity, and perceptions of career interest of students of the Semarang City Islamic Banking Study Program in Islamic Banking both simultaneously and partially. The population in this study were students of the Islamic Banking Study Program in Semarang City. Using a sampling technique, namely purposive and accidental sampling, 100 respondents met the criteria. The data used in this study are primary data obtained through distributing questionnaires. The analysis model used in this study is a multiple linear regression analysis model. In contrast, the analysis technique uses the F statistical test, the coefficient of determination (R2) test, and the t statistical test, which is processed using the SPSS 25.00 program. The hypothesis proving and discussion results show that Islamic Banking Knowledge, Social Values, Religiosity, and Perceptions significantly affect student career interest in Islamic Banking. Sharia Banking Knowledge and Social Values partially have a positive effect but do not substantially affect student career interest in Islamic Banking. Religiosity partially has a positive and significant impact on student career interest in Islamic Banking. Perception partially has a positive and significant effect on students' career interest in Islamic Banking.